2020
DOI: 10.3892/ol.2020.12209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AK4 as a novel therapeutic target for serous ovarian cancer

Abstract: The present study aimed to assess the expression level of adenylate kinase 4 (AK4) in human serous ovarian cancer (SOC) tissues and investigate the possible involvement of AK4 in SOC progression. Bioinformatics analysis based on The Cancer Genome Atlas (TCGA) database and immunohistochemical (IHC) assays were performed to assess the expression level of AK4 in human SOC tissues. Clinical pathological features of patients with SOC were also evaluated. Colony formation, MTT, wound healing and Transwell assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…This indicates that AK4 plays an essential role in PASMCs not only by regulating cellular responses to hypoxia but also under physiological conditions. Similar effects of AK4 targeting have been described for immortalized human embryonic kidney cells [ 33 ] and some cancer cell lines [ 28 , 29 , 37 ]. This points to a common fundamental role of AK4 in cancer cells and PASMCs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This indicates that AK4 plays an essential role in PASMCs not only by regulating cellular responses to hypoxia but also under physiological conditions. Similar effects of AK4 targeting have been described for immortalized human embryonic kidney cells [ 33 ] and some cancer cell lines [ 28 , 29 , 37 ]. This points to a common fundamental role of AK4 in cancer cells and PASMCs.…”
Section: Discussionsupporting
confidence: 67%
“…In humans, nine adenylate kinase isoenzymes (AK1–AK9) are known, displaying different organ and subcellular distributions, kinetic properties, and functions in response to diverse physiological and pathological stimuli [ 19 , 20 , 21 ]. A rapidly growing body of research unveils the importance of AK isoenzymes in the regulation of numerous cellular processes, including cell differentiation and proliferation, motility, metabolic reprogramming, and cancer progression [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…During our studies, we found an overwhelming amount of literature support, demonstrating that the majority of our identified biomarkers had confirmed roles in signaling pathways confirmed in cancer progression, validating their potential as prognosis biomarkers in CAW-TNBCs. AK4, observed to be down-regulated in our studies, is involved in the progression of Serous ovarian cancer [81], and AK4 depletion was shown to impair cell proliferation and invasion in MCF7 as well as MB231 breast cancer cells [82]. CAV1, a tumor suppressor gene candidate, is a negative regulator of the Ras-p42/44 mitogen-activated kinase cascade [83], and has been shown to play a critical role in the progression of breast cancer through autophagy, invasion, proliferation, apoptosis, migration, and breast cancer metastasis [84].…”
Section: Discussionmentioning
confidence: 94%
“…There is considerable research showing that AK4 is a prognostic marker in several types of cancer, including ovarian cancer and bladder cancer, where an increased expression of AK4 is usually associated with poorer patient survival. In lung cancer, elevated AK4 expression could promote metastasis by downregulating the transcription factor ATF3, which leads to MMP2 induction .…”
Section: Resultsmentioning
confidence: 99%